Judge as Conscientious Objector – Analysis Based on Cultural Exemptions Theory and U.S. Law - Mazurkiewicz, Szymon (Polish Review of International and European Law, 2018)
The aim of this paper is to analyze whether it is possible for a judge to possess the right to conscientious objection. Firstly, the author provides some conceptual remarks along with distinguishing conscientious objection from other situations concerning conflict between law and morality that involve judges. Next, cultural exemptions/religious accommodations theory is introduced as a conceptual basis for further analysis. W. Ciszewski’s multidimensional view on exemption theory is applied here. It distinguishes three levels of discussion: the general legitimatization of accommodations, secondly, the justification of a concrete exemption and thirdly the scope, process of application and exclusions of the specific exemption. This paper involves the second level and some issues from the third. Five premises given by W. Ciszewski are considered: (1) significance of a goal realized by regulation, (2) formal amenability of a duty to exclusion, (3) significance of one’s world view being in conflict with duty, (4) prohibition of the unjustified privileging of a group and (5) size of a group that may obtain an exemption. The last part involves the problem of applying a conscience clause. In the paper the author analyzes whether the regulation of judicial disqualification, especially judicial recusal, can be regarded as a legal basis for taking advantage of conscientious objection. The author also considers the boundaries of the clause of conscience with special emphasize on the individual’s right to a fair trial.